HASIL BELAJAR KOGNITIF IPA FISIKA SISWA MELALUI PENERAPAN MODEL KOOPERATIF TIPE NUMBERED HEAD TOGETHER DI KELAS VIIIB MTs. DINIYAH PUTRI PEKANBARU - Vinni Elvionita Elvionita; Zulhelmi '; Syahril ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research was intended to describe the results cognitive learning physical science of students by using cooperative model Type Numbered Head Together in physics learning for subject matter of pressure. Type of research is Pre-Experiment by The One-Shot Case Study design. That conducted a research toward of 23 students in grade VIIIB MTs Diniyah Putri Pekanbaru 2014/2015 school year. The instrument of the research was the results of cognitive learning test that given after learning and analyzed descriptively. The result descriptive showed absorptive capacity of the average students was 80,09 % in good category, learning affectiveness was 80,09 % in effective category, completeness learning students in classical was 73,91 % in incomplete category, completeness in classical indicators was 73,68 % in incomplete category. The result showed that implementation of cooperative model Type Numbered Head Together can improved liveliness in gruop and give good result of cognitive learning students in  individual  in physical science. Key word: result cognitive learning, Numbered Head Together, Pressure, physical science